English language teaching materials - Harwood, Nigel (Cambridge University, 2014)
Includes bibliographical references and indexes; "This volume provides an incisive overview of the current state of materials design in language teaching. Seventeen original chapters explore the issues involved in the design, implementation, and evaluation of materials in language programs in a wide variety of settings and contexts. This stimulating collection considers different approaches to materials design - including teacher-developed classroom materials, commercial materials, and technology-driven materials. Discussion questions and tasks follow each chapter to make this volume useful to both prospective and practicing teachers alike"--Provided by publisher